1985
DOI: 10.1177/002221948501800304
|View full text |Cite
|
Sign up to set email alerts
|

Few CT Scan Abnormalities Found Even in Neurologically Impaired Learning Disabled Children

Abstract: Computerized tomography (CT) scans without enhancement were performed on 32 children attending a learning disabilities clinic. These 32 were selected because they had subtle lateralizing neurological hemisyndromes (16 right, 16 left). Clinical readings of 25 scans by two independent radiologists “blind” to neurological or historical facts yielded only 5 (20%) concordant abnormal readings. Measurements of ventricular size in all 32 scans yielded even fewer (only 1) judged abnormal. Meaningful hemispheric asymme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…A second approach, typical of the Haslam, Dalby, Johns, and Rademaker (1981) and Denckla, LeMay, and Chapman (1985) studies, was to examine CT findings in relation to clinically defined subgroups. In the Haslam et al (1981) study, Boder's (1973) dysphonetic, dyseidetic, and nonspecific subtypes were used, whereas in Denckla et al's (1985) study, the subjects were chosen to represent children with left or right hemisyndromes (based primarily on lateralizing motor signs). In these studies, the relation between subgroups on measures of cerebral asymmetry or symmetry and other variables including intelligence and birth history were examined.…”
Section: Neuroimaging Studies (Ct/mri)mentioning
confidence: 99%
See 3 more Smart Citations
“…A second approach, typical of the Haslam, Dalby, Johns, and Rademaker (1981) and Denckla, LeMay, and Chapman (1985) studies, was to examine CT findings in relation to clinically defined subgroups. In the Haslam et al (1981) study, Boder's (1973) dysphonetic, dyseidetic, and nonspecific subtypes were used, whereas in Denckla et al's (1985) study, the subjects were chosen to represent children with left or right hemisyndromes (based primarily on lateralizing motor signs). In these studies, the relation between subgroups on measures of cerebral asymmetry or symmetry and other variables including intelligence and birth history were examined.…”
Section: Neuroimaging Studies (Ct/mri)mentioning
confidence: 99%
“…Of even more serious concern, however, is the fact that reading achievement, or delays in reading achievement, are not documented in several studies (e.g., Denckla et al, 1985; Leisman & Ashkenazi, 1980; Rosenberger & Hier, 1980). Furthermore, in opposition to recommendations made by pertinent professional organizations (e.g., National Council on Measurement in Education, International Reading Association), who oppose the reporting and analysis of grade equivalent scores because of their derived psychometric properties and misrepresentation of actual levels of achievement (Hynd & Cohen, 1983), a number of studies report reading achievement in grade equivalent (GE) scores (Haslam et al, 1981; Hier et al, 1978; Rumsey et al, 1986).…”
Section: Neuroimaging Studies (Ct/mri)mentioning
confidence: 99%
See 2 more Smart Citations
“…The components of the traditional neurological assessment include an electroencephalogram (EEG), a brain scan, and skull x-rays. Unfortunately, there is a lack of conclusive research indicating that hyperactive children can be reliably identified using these assessment techniques (Denckla, LeMay, & Chapman, 1985;Satterfield, Lesser, Saul, & Cantwell, 1973). Nonetheless, current research in neuroradiological techniques such as nuclear magnetic resonance indicate that traditional neurological assessments may soon be more effective in the identification of hyperactivity (Johnston, 1987).…”
Section: Biophysical Componentsmentioning
confidence: 99%